Spontaneous Single-Molecule Dissociation in Infrared Nanocavities - Herrera-Urbina, F (American Institute of Physics, 2025)
Ultrastrong light-matter interaction with molecular vibrations in infrared cavities has emerged as a tool for manipulating and controlling chemical reactivity. By studying the wavepacket dynamics of an individual polar diatomic molecule in a quantized infrared electromagnetic environment, we show that chemical bonds can efficiently dissociate in the absence of additional thermal or coherent energy sources, provided that the coupled system is prepared in a suitable diabatic state. Using hydrogen fluoride as a case study, we predict dissociation probabilities of up to 35% in less than 200 fs for a vibration-cavity system that is rapidly initialized with a low number of bare vibrational and cavity excitations. We develop a simple and general analytical model based on the multipolar formulation of quantum electrodynamics to show that the Bloch-Seigert shift of the bare vibrational ground state is a predictor of a threshold coupling strength below which no spontaneous dissociation is expected. The role of state-dependent permanent dipole moments in the light-matter interaction process is clarified. Our work paves the way toward the development of vacuum-assisted chemical reactors powered by ultrastrong light-matter interaction at the single-molecule level. © 2025 Author(s).